Hydrogel and preparation method thereof

By using a hydrogel dressing that combines polyvinyl alcohol and metal salts, and using freeze-thaw technology to form a physical cross-linked structure, the problem of using toxic cross-linking agents in the preparation process of existing hydrogel dressings is solved, and an efficient and safe solution is achieved. Wound treatment effect and simplified preparation process.

CN119331371APending Publication Date: 2025-01-21BEIJING ZENITHNANO TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411541897.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

During the preparation process, existing hydrogel dressings require additional components such as crosslinkers and initiators, which may lead to the risk of toxic monomer residues and increased costs, and it is difficult to meet the needs of the elderly and other special groups in wound treatment.

Method used

The use of polyvinyl alcohol and metal salt as the main ingredient, the physical cross -linking structure is formed by freezing technology, avoiding the use of chemical cross -linking agents, simplifying the preparation process, and regulating the amount of metal salt to achieve different degrees of antibacterial effects.

Benefits of technology

It provides an efficient and safe hydrogel dressing with good antibacterial properties, mechanical strength and toughness, is suitable for long-term use, reduces the risk of wound infection, and has a simple and cost-effective preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331371A_ABST
    Figure CN119331371A_ABST
Patent Text Reader

Abstract

The invention relates to hydrogel and a preparation method thereof, and relates to the technical field of hydrogel, the hydrogel comprises polyvinyl alcohol and metal salt, the final concentration of the polyvinyl alcohol is 8-12 wt%, and the final concentration of the metal salt is 0.1-0.5 mol / L. According to the hydrogel disclosed by the invention, an efficient and safe technical solution is provided by combining the biological safety of the polyvinyl alcohol and the broad-spectrum antibacterial performance of various metal salts; the addition amount of the metal salt in the hydrogel can be adjusted according to specific requirements, so that different degrees of antibacterial effects are achieved, meanwhile, good safety and stability are kept, polyvinyl alcohol serving as a main component has extremely high biological safety and biocompatibility, is free of toxic and side effects on a human body, is suitable for wound treatment and has wide application prospects. Metal ions act on microbial cells through a plurality of mechanisms, including oxidative stress, protein dysfunction and cell membrane damage, so that the propagation of bacteria is effectively blocked, and the growth of the bacteria is killed or inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of hydrogel technology, and in particular to a hydrogel and a preparation method thereof. Background Art

[0002] As the aging process of society intensifies, the risk of wound infection in the elderly has increased significantly, which may not only delay the healing process of wounds, but also pose a serious threat to the health of the elderly and bring great inconvenience to their daily lives. Traditional wound dressings mostly rely on materials such as gauze, cotton wool, plasters, and bandages, which usually carry antibacterial substances such as antibiotics to prevent wound infection. However, a large amount of wound exudate may make these traditional dressings moist and difficult to remove, limiting their effectiveness in long-term use.

[0003] Polyvinyl alcohol (PVA) is a widely used water-soluble polymer that can quickly dissolve in water to form a stable colloid. Due to its non-toxic, harmless and biosafe properties, PVA hydrogel dressings have been widely used in the biomedical field, such as drug delivery systems, wound treatment and contact lenses. Compared with traditional dressings, hydrogel dressings can effectively solve the problems of wound moisture and adhesion, providing a new wound treatment method. However, the current preparation process of hydrogel dressings usually requires the addition of cross-linking agents, initiators and other ingredients to ensure its stability, which may lead to the risk of toxic monomer residues and increased costs.

[0004] Therefore, seeking new methods for preparing hydrogel dressings that do not contain harmful substances has become an important direction of current research, in order to further improve the safety and sustainability of dressings and meet the needs of the elderly and other special groups in wound treatment. Summary of the invention

[0005] In order to solve the problem that existing hydrogel dressings contain harmful substances, the present application provides a hydrogel and a preparation method thereof.

[0006] The present application provides a hydrogel and a preparation method thereof using the following technical solutions: A hydrogel comprises polyvinyl alcohol and a metal salt, wherein the final concentration of the polyvinyl alcohol is 8-12wt%, and the final concentration of the metal salt is 0.1-0.5 mol / L.

[0007] By adopting the above technical scheme, the hydrogel of the present application provides an efficient and safe technical solution for wound treatment and chronic wound healing by combining the biosafety of polyvinyl alcohol and the broad-spectrum antibacterial properties of various metal salts; polyvinyl alcohol as the main component has extremely high biosafety and biocompatibility, is non-toxic to the human body, has no side effects, and is suitable for long-term contact with the skin. For example, when used in wound treatment, metal ions act on microbial cells through various mechanisms, including oxidative stress, protein dysfunction and cell membrane damage, effectively blocking the spread of bacteria, thereby killing or inhibiting the growth of bacteria. The antibacterial hydrogel containing metal ions maintains a high sterilization rate while still maintaining good safety, and is suitable for long-term use. The amount of metal salt added in the hydrogel of the present application can be adjusted according to specific needs to achieve different degrees of antibacterial effects while maintaining good safety and stability.

[0008] In a specific embodiment, the metal salt is one of sodium chloride, magnesium chloride, zinc chloride, aluminum chloride hexahydrate, and ferric chloride.

[0009] By adopting the above technical scheme, the above metal salts all have antibacterial effects, destroy the cell walls of microorganisms or inhibit their metabolic activity through different mechanisms, effectively inhibit the growth and reproduction of various bacteria, thereby reducing the risk of wound infection. The presence of metal salts in the hydrogel provides long-lasting antibacterial protection, prolongs the duration of the therapeutic effect, and reduces the possibility of secondary infection of the wound.

[0010] In a specific embodiment, the average molecular weight of the polyvinyl alcohol is 89,000-98,000 Mw, and the alcoholysis degree of the polyvinyl alcohol is >99%.

[0011] By adopting the above technical solution, a high alcoholysis degree is used to make the PVA molecular chain contain a large number of hydroxyl groups, making it easily soluble in water. The high alcoholysis degree is related to biocompatibility, making it suitable for medical materials or biomedical applications. This polymer remains stable in a variety of environments and is suitable for long-term use or complex application conditions. The appropriate molecular weight provides good mechanical strength and toughness, making it suitable for structural applications with higher requirements.

[0012] In a specific embodiment, the hydrogel further comprises glycerol and water, the final concentration of the glycerol is 12-18 wt %, and the mass ratio of the glycerol to water is 2:8.

[0013] By adopting the above technical solution, glycerol can improve the texture of the hydrogel and make it smoother. Mixing with water can optimize the touch of the gel. This ratio enables the hydrogel to maintain good fluidity and stability in a variety of application scenarios, making it feel more comfortable when used on the skin. The presence of glycerol increases the viscoelasticity of the hydrogel, which enables the gel to better maintain its shape during use and provide a more lasting effect. This property helps to improve the product's usage experience, especially in drug delivery and skin care applications.

[0014] In a specific embodiment, the swelling ratio of the hydrogel is 280%-390%.

[0015] By adopting the above technical scheme, the above parameters show that the hydrogel has a very high water absorption capacity, which enables it to effectively absorb and retain a large amount of water in a variety of applications and is suitable for occasions that require a large amount of water retention, such as medical dressings and moisturizing products.

[0016] In a specific embodiment, the antibacterial rate of the hydrogel is 95%-100%.

[0017] In a specific embodiment, the elastic modulus of the hydrogel is 15-38 kPa.

[0018] By adopting the above technical scheme, the above parameters indicate that the hydrogel has moderate flexibility and elasticity, so that it can provide good comfort, cushioning performance and structural stability in various applications, and help protect compressed or impacted surfaces. This property enables the hydrogel to adapt to deformation while maintaining its shape, helps maintain stable gel properties, and can adapt to various shapes and surfaces. It is particularly suitable for products that require softness and comfort, such as medical dressings and skin care products.

[0019] In a specific embodiment, the tensile strength of the hydrogel is 85-227 kPa.

[0020] By adopting the above technical solution, the above parameters indicate that the hydrogel has good mechanical strength and can maintain structural integrity when subjected to tensile force, so that it exhibits good stability and strength when subjected to external force. By utilizing this tensile strength range, the hydrogel can resist stretching and friction when used as a wound dressing and provide lasting protection.

[0021] In a specific embodiment, the elongation of the hydrogel is 2.5-2.8 times.

[0022] By adopting the above technical solution, the elongation range of 2.5-2.8 times indicates that the hydrogel can be significantly deformed and not easily broken when subjected to force. This elongation allows the hydrogel to effectively adapt to the natural movement and stretching of the skin, reduce rupture caused by friction or movement, and improve the comfort of wound healing.

[0023] In a specific embodiment, the degradation temperature of the hydrogel is ≥ 60°C.

[0024] By adopting the above technical solution and utilizing the above parameter design, due to the high degradation temperature of the hydrogel, it can remain stable in hot or high-temperature environments and will not degrade prematurely or lose its efficacy, thereby ensuring long-term and effective wound protection and treatment effects. The stability and lasting antibacterial effect in high-temperature environments can reduce the need for frequent product replacement, thereby reducing overall care costs and improving cost-effectiveness. In addition, after the end of its service life, the hydrogel can be effectively degraded, and the degradation products have little impact on the environment, which meets the requirements of modern society for environmentally friendly products.

[0025] In a specific embodiment, the hydrogel is prepared by freeze-thaw technique.

[0026] By adopting the above technical scheme and using freeze-thaw technology to prepare, the uniformity and stability of the hydrogel can be effectively improved, ensuring that the metal salt and polyvinyl alcohol are fully mixed and distributed during the preparation process, thereby enhancing the consistency of the product and the controllability of the effect. The crystalline or gel network structure formed during the freeze-thaw process helps to improve the water absorption and swelling of the hydrogel, further improve the wound moisturizing effect and cell permeability, and promote wound healing. The freeze-thaw process can enhance the interaction between the metal salt and the polyvinyl alcohol matrix, improve the release efficiency and antibacterial activity of metal ions, and thus enhance the antibacterial ability of the hydrogel.

[0027] A method for preparing a hydrogel comprises the following steps: S1. Prepare polyvinyl alcohol, metal salt, glycerol and water; S2, dissolving the polyvinyl alcohol, the glycerol and the water at a temperature of 85° C.-95° C. for 1 h-1.5 h to form a mixed solution, and then cooling the dissolved mixed solution to 30° C.-40° C.; S3, adding the metal salt into the mixed solution, reacting for 1h-1.5h, and standing to defoam, to obtain a hydrogel solution; S4, after defoaming, pour the hydrogel solution into a mold, freeze it in a -20°C-30°C environment for 6h-18h, and then thaw it at 20°C-30°C for 1h-3h to form a physically cross-linked hydrogel; S5. Repeat the freezing and thawing steps in S4 for 3 times, take out the mixture from the mold, and obtain the hydrogel.

[0028] By adopting the above technical scheme, the method of the present application only needs to dissolve polyvinyl alcohol, add metal salt, and then perform freeze-thaw treatment, without the need for additional cross-linking agents or initiators, and the hydrogel can be formed only through the freeze-thaw process, and the preparation process is relatively simple and economical; through the freezing and thawing process, the molecular chains of polyvinyl alcohol form a physical cross-linked structure at a specific temperature, and this structure is tightly bound by physical effects such as van der Waals forces and hydrogen bonds, and the formation of hydrogel can be achieved without chemical cross-linking agents, and through multiple freeze-thaw cycles, the physical and mechanical properties of the hydrogel are significantly improved, and each freezing will form a new ordered micro-region (physical cross-linking point), which enhances the structural stability and strength of the hydrogel; due to the characteristics of physical cross-linking and the presence of glycerol, the hydrogel prepared by freeze-thaw can maintain stable performance in a wide temperature range, including high temperature and low temperature resistance, and this hydrogel can be widely used in medical, industrial and other fields; The hydrogel prepared by the method of the present application has the advantages of simple preparation, stable physical cross-linked structure, improved physical properties, environmental friendliness and wide application potential, etc. This method not only reduces production costs, but also can meet the needs of various industrial and medical fields.

[0029] In a specific embodiment, in the hydrogel prepared by the preparation method: the final concentration of the polyvinyl alcohol is 8-12wt%, the final concentration of the metal salt is 0.1-0.5 mol / L, the final concentration of the glycerol is 12-18wt%, and the mass ratio of the glycerol to the water is 2:8.

[0030] In summary, the beneficial technical effects of this application are: 1. The hydrogel of the present application provides an efficient and safe technical solution for wound treatment and chronic wound healing by combining the biosafety of polyvinyl alcohol and the broad-spectrum antibacterial properties of various metal salts; and the amount of metal salt added to the hydrogel of the present application can be adjusted according to specific needs to achieve different degrees of antibacterial effect while maintaining good safety and stability; 2. The method of the present application only requires dissolving polyvinyl alcohol glycerol and water, adding metal salts, and then performing freeze-thaw treatment. No additional cross-linking agent or initiator is required. The hydrogel can be formed only through the freeze-thaw process, and the preparation process is relatively simple and economical. Through the freezing and thawing process, the molecular chains of polyvinyl alcohol form a physical cross-linked structure at a specific temperature. This structure is tightly bound by physical effects such as van der Waals forces and hydrogen bonds. The formation of hydrogel can be achieved without chemical cross-linking agents, and the physical and mechanical properties of the hydrogel are significantly improved through multiple freeze-thaw cycles. Each freezing will form a new ordered micro-region (physical cross-linking point), enhancing the structural stability and strength of the hydrogel. This method not only reduces production costs, but also can meet the needs of various industrial and medical fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram showing hydrogels prepared using different metal salts. DETAILED DESCRIPTION

[0032] The following is combined with Figure 1 This application is described in further detail.

[0033] The present application provides a hydrogel. In this embodiment, the hydrogel includes but is not limited to being used in the biomedical field. The hydrogel includes but is not limited to being used as a wound dressing; The hydrogel includes polyvinyl alcohol and a metal salt, wherein the final concentration of the polyvinyl alcohol is 8-12wt%. In this embodiment, preferably, the final concentration of the polyvinyl alcohol is 10wt%, and the final concentration of the metal salt is 0.1-0.5 mol / L. In this embodiment, preferably, the final concentration of the metal salt is 0.2-0.3 mol / L. In the wound dressing, a metal salt concentration of 0.2-0.3 mol / L can provide a moderate degree of cross-linking, so that the dressing has good mechanical strength and flexibility, while maintaining a certain water absorption and comfort. In this embodiment, the metal salt includes but is not limited to one of sodium chloride (NaCl), magnesium chloride (MgCl2), zinc chloride (ZnCl2), aluminum chloride hexahydrate (AlCl3·6H2O), and ferric chloride (PVA-FeCl3); metal salts such as sodium chloride, magnesium chloride, zinc chloride, aluminum chloride hexahydrate, and ferric chloride all have antibacterial effects, destroying microbial cell walls or inhibiting their metabolic activity through different mechanisms, effectively inhibiting the growth and reproduction of various bacteria, thereby reducing the risk of wound infection. The presence of metal salts in the hydrogel provides long-lasting antibacterial protection, prolongs the duration of the treatment effect, and reduces the possibility of secondary infection of the wound.

[0034] The average molecular weight of polyvinyl alcohol is 89000-98000 Mw, and the alcoholysis degree of polyvinyl alcohol is greater than 99%. By using polyvinyl alcohol with a higher alcoholysis degree, a large number of hydroxyl groups (-OH) are contained in its molecular chain, making it easily soluble in water. A high alcoholysis degree is related to biocompatibility, making it suitable for use in medical materials or biomedical applications. This polymer remains stable in a variety of environments and is suitable for long-term use or complex application conditions. The appropriate molecular weight provides good mechanical strength and toughness, making it suitable for structural applications with higher requirements.

[0035] The hydrogel also includes glycerol and water, and the final concentration of glycerol is 12-18wt%. In this embodiment, preferably, the final concentration of glycerol is 15wt%, and the mass ratio of glycerol to water is 2:8; glycerol can improve the texture of the hydrogel and make it smoother, and mixing with water can optimize the touch of the gel. This ratio enables the hydrogel to maintain good fluidity and stability in a variety of application scenarios, making it feel more comfortable when used on the skin; the presence of glycerol increases the viscoelasticity of the hydrogel, which enables the gel to better maintain its shape during use and provide a more lasting effect. This property helps to improve the product's usage experience, especially in drug delivery and skin care applications.

[0036] In this embodiment, the hydrogel is prepared by freeze-thaw technology; freeze-thaw technology preparation can effectively improve the uniformity and stability of the hydrogel, ensure that the metal salt and polyvinyl alcohol are fully mixed and distributed during the preparation process, thereby enhancing the consistency of the product and the controllability of the effect. The crystalline or gel network structure formed during the freeze-thaw process helps to improve the water absorption and swelling of the hydrogel, further improve the wound moisturizing effect and cell permeability, and promote wound healing. The freeze-thaw process can enhance the interaction between the metal salt and the polyvinyl alcohol matrix, improve the release efficiency and antibacterial activity of metal ions, thereby enhancing the antibacterial ability of the hydrogel.

[0037] In this embodiment, the hydrogel can achieve 95-100% antibacterial effect in 7 days at room temperature. It can effectively inhibit the growth or activity of most bacteria, and it has high efficiency and long-lasting antibacterial properties, making it have wide application potential in medical treatment, personal care and other fields that require antibacterial protection; The swelling rate of the hydrogel is 280%-390%; it has a very high water absorption capacity, which enables the hydrogel to effectively absorb and retain a large amount of water in a variety of applications, and is suitable for occasions that require a large amount of water retention, such as medical dressings and moisturizing products; In this embodiment, the swelling rate of PVA-NaCl hydrogel at 24 h is 310%, the swelling rate of PVA-MgCl2 hydrogel at 24 h is 310%, the swelling rate of PVA-ZnCl2 hydrogel at 24 h is 389%, the swelling rate of PVA-AlCl3·6H2O hydrogel at 24 h is 322%, and the swelling rate of PVA-FeCl3 hydrogel at 24 h is 287%.

[0038] The elastic modulus of the hydrogel is 15-38kPa; it has moderate flexibility and elasticity, which enables it to provide good comfort, cushioning performance and structural stability in various applications, and helps to protect surfaces that are compressed or impacted. This property enables the hydrogel to adapt to deformation while maintaining its shape, helps maintain stable gel properties, and can adapt to various shapes and surfaces. It is especially suitable for products that require softness and comfort, such as medical dressings and skin care products; The tensile strength of the hydrogel is 85-227 kPa; it has good mechanical strength and can maintain structural integrity when subjected to tensile force, so that it exhibits good stability and strength when subjected to external force. By using this tensile strength range, the hydrogel can resist stretching and friction when used as a wound dressing, providing long-lasting protection; The elongation of the hydrogel is 2.5-2.8 times; thus, the hydrogel can be significantly deformed when subjected to force without breaking easily. This elongation allows the hydrogel to effectively adapt to the natural movement and stretching of the skin, reduce rupture caused by friction or movement, and improve the comfort of wound healing; In this embodiment, the elastic modulus of the PVA-NaCl hydrogel reaches 38 KPa (0-50%), the tensile strength reaches 227 KPa, and it can be stretched 2.8 times; the elastic modulus of the PVA-MgCl2 hydrogel reaches 26.8 KPa (0-50%), the tensile strength reaches 165 KPa, and it can be stretched 2.8 times; the elastic modulus of the PVA-ZnCl2 hydrogel reaches 15.2 KPa (0-50%), the tensile strength reaches 85.8 KPa, and it can be stretched 2.5 times; the elastic modulus of the PVA-AlCl3·6H2O hydrogel reaches 30.4 KPa (0-50%), the tensile strength reaches 158.2 KPa, and it can be stretched 2.8 times; the elastic modulus of the PVA-FeCl3 hydrogel reaches 20.8 KPa (0-50%), the tensile strength reaches 193.6 KPa, and it can be stretched 2.6 times.

[0039] The degradation temperature of the hydrogel is ≥60°C; due to the high degradation temperature of the hydrogel, it can remain stable in hot or high-temperature environments and will not degrade prematurely or lose its efficacy, ensuring long-term and effective wound protection and treatment effects. The stability and lasting antibacterial effect in high-temperature environments can reduce the need for frequent product replacement, thereby reducing overall care costs and improving cost-effectiveness. In addition, the hydrogel can be effectively degraded after the end of its service life, and the degradation products have little impact on the environment, which meets the requirements of modern society for environmentally friendly products.

[0040] The hydrogel of the present application provides an efficient and safe technical solution for wound treatment and chronic wound healing by combining the biosafety of polyvinyl alcohol and the broad-spectrum antibacterial properties of various metal salts; polyvinyl alcohol as the main ingredient has extremely high biosafety and biocompatibility, is non-toxic to the human body, has no side effects, and is suitable for long-term contact with the skin. For example, when used in wound treatment, metal ions act on microbial cells through various mechanisms, including oxidative stress, protein dysfunction, and cell membrane damage, effectively blocking the spread of bacteria, thereby killing or inhibiting the growth of bacteria. The antibacterial hydrogel containing metal ions maintains a high sterilization rate while still maintaining good safety, and is suitable for long-term use. The amount of metal salt added to the hydrogel of the present application can be adjusted according to specific needs to achieve different degrees of antibacterial effects while maintaining good safety and stability.

[0041] The present application provides a method for preparing a hydrogel, referring to Figure 1 , Figure 1 Used to demonstrate the morphological structure of hydrogels made with different metal salts, the method adopts the following technical scheme: S1. Prepare polyvinyl alcohol, metal salt, glycerol and water. In this embodiment, the metal salt includes but is not limited to one of sodium chloride (NaCl), magnesium chloride (MgCl2), zinc chloride (ZnCl2), aluminum chloride hexahydrate (AlCl3·6H2O) and ferric chloride (FeCl3). In this embodiment, the properties of the hydrogels prepared from different metal salts are shown in Table 1. S2, dissolving polyvinyl alcohol, glycerol and water at 85°C-95°C for 1h-1.5h to form a mixed solution, and then cooling the dissolved mixed solution to 30°C-40°C; in this embodiment, preferably, dissolving polyvinyl alcohol, glycerol and water at 90°C for 1h, and then cooling the dissolved mixed solution to 35°C; S3, adding metal salt to the mixed solution, reacting for 1h-1.5h, and standing to defoam, to obtain a hydrogel solution; in this embodiment, preferably, the mixed solution of polyvinyl alcohol, glycerol and water is reacted with the metal salt for 1h to ensure that the metal salt and polyvinyl alcohol react fully to form a stable hydrogel solution. During the mixing process, foam may be generated, so defoaming treatment is required, and the mixed solution is allowed to stand to allow the foam to disappear naturally to form a uniform hydrogel solution; S4, after defoaming, pour the hydrogel solution into a mold, freeze it in an environment of -20°C--30°C for 6h-18h, and then thaw it at 20°C-30°C for 1h-3h, so as to form a physically cross-linked PVA hydrogel; in this embodiment, preferably, after defoaming, pour the hydrogel solution into a mold, freeze it in an environment of -30°C for 12h, and then thaw it at 25°C for 1h, so as to form a physically cross-linked PVA hydrogel; S5. The mixed solution is subjected to three freezing and thawing cycles to enhance the effect of physical crosslinking. Each freezing and thawing step is performed according to the operation in S4. Repeated treatment helps to improve the crosslinking degree of the hydrogel, so that it has better structural stability and mechanical properties. After completing all freezing and thawing cycles, the final hydrogel product is taken out from the mold. At this time, the hydrogel has formed a physically crosslinked network structure with good elasticity and mechanical properties. In this embodiment, the physical and mechanical properties of the hydrogel under different freezing and thawing times are shown in Table 2.

[0042] In this embodiment, in the hydrogel prepared by the preparation method, the final concentration of polyvinyl alcohol is 8-12wt%, the final concentration of the metal salt is 0.1-0.5 mol / L, the final concentration of glycerol is 12-18wt%, and the mass ratio of glycerol to the water is 2:8; The method of the present application only requires dissolving polyvinyl alcohol, glycerol, and water, adding metal salts, and then performing freeze-thaw treatment. No additional cross-linking agent or initiator is required. The hydrogel can be formed only through the freeze-thaw process, and the preparation process is relatively simple and economical. Through the freezing and thawing process, the molecular chains of polyvinyl alcohol form a physical cross-linked structure at a specific temperature. This structure is tightly bound by physical effects such as van der Waals forces and hydrogen bonds. The formation of the hydrogel can be achieved without a chemical cross-linking agent, and the physical and mechanical properties of the hydrogel are significantly improved through multiple freeze-thaw cycles. Each freezing will form a new ordered micro-region (physical cross-linking point), which enhances the structural stability and strength of the hydrogel. Due to the physical cross-linking characteristics and the presence of glycerol, the hydrogel prepared by freeze-thawing can maintain stable performance over a wide temperature range, including high and low temperature resistance. This hydrogel can be widely used in medical, industrial and other fields. The hydrogel prepared using the method of the present application has the advantages of simple preparation, stable physical cross-linking structure, improved physical properties, environmental friendliness and wide application potential. This method not only reduces production costs, but also can meet the needs of various industrial and medical fields.

[0043] Example Table 1 Hydrogel properties of different metal salts The following conclusions can be drawn from the table above: Different metal salts have a significant effect on the swelling properties of hydrogels. The hydrogels caused by ZnCl2 have the strongest water absorption, which is consistent with the 2+ The charge density of ions is related to the interaction with PVA chains. NaCl and MgCl2 show similar swelling behaviors, while FeCl3 has the lowest swelling rate. The hydrogel provided by NaCl has the highest rigidity, which indicates that Na +The ions enhanced the cross-linking of PVA chains or caused stronger physical cross-linking; PVA-NaCl hydrogel performed best in terms of elastic modulus and had a higher swelling rate, so PVA-NaCl hydrogel can be considered the optimal choice.

[0044] Table 2 Properties of hydrogels at different freezing and thawing times The following conclusions can be drawn from the above table: the number of freezing and thawing has a significant effect on the viscosity and elasticity of the hydrogel. The more times of freezing and thawing, the lower the viscosity of the hydrogel, while the elasticity increases. This shows that by increasing the number of freezing and thawing, the flexibility and elasticity of the hydrogel can be improved; in this embodiment, if the hydrogel is required to have higher elasticity and lower viscosity, then freezing and thawing 3 times is the best choice.

[0045] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A hydrogel, characterized in that: The hydrogel comprises polyvinyl alcohol and a metal salt, wherein the final concentration of the polyvinyl alcohol is 8-12 wt %, and the final concentration of the metal salt is 0.1-0.5 mol / L.

2. The hydrogel according to claim 1, characterized in that: The metal salt is one of sodium chloride, magnesium chloride, zinc chloride, aluminum chloride hexahydrate and ferric chloride.

3. The hydrogel according to claim 1, characterized in that: The average molecular weight of the polyvinyl alcohol is 89000-98000 Mw, and the alcoholysis degree of the polyvinyl alcohol is greater than 99%.

4. The hydrogel according to claim 1, characterized in that: The hydrogel also includes glycerol and water, the final concentration of the glycerol is 12-18wt%, and the mass ratio of the glycerol to water is 2:

8.

5. The hydrogel according to claim 1, characterized in that: The swelling rate of the hydrogel is 280%-390%.

6. The hydrogel according to claim 1, characterized in that: The antibacterial rate of the hydrogel is 95%-100%.

7. The hydrogel according to claim 1, characterized in that: The elastic modulus of the hydrogel is 15-38 kPa.

8. The hydrogel according to claim 1, characterized in that: The tensile strength of the hydrogel is 85-227 kPa.

9. The hydrogel according to claim 1, characterized in that: The elongation of the hydrogel is 2.5-2.8 times.

10. The hydrogel according to claim 1, characterized in that: The dissolution temperature of the hydrogel is ≥60°C.

11. The hydrogel according to claim 1, characterized in that: The hydrogel is prepared by freeze-thaw technology.

12. A method for preparing a hydrogel, characterized in that: The following steps are involved: S1. Prepare polyvinyl alcohol, metal salt, glycerol and water; S2, dissolving the polyvinyl alcohol, the glycerol and the water at a temperature of 85° C.-95° C. for 1 h-1.5 h to form a mixed solution, and then cooling the dissolved mixed solution to 30° C.-40° C.; S3, adding the metal salt into the mixed solution, reacting for 1h-1.5h, and standing to defoam, to obtain a hydrogel solution; S4, after defoaming, pour the hydrogel solution into a mold, freeze it in a -20℃-30℃ environment for 6h-18h, and then thaw it at 20℃-30℃ for 1h-3h to form a physically cross-linked hydrogel; S5. Repeat the freezing and thawing steps in S4 for 3 times, take out the mixture from the mold, and obtain the hydrogel.

13. The preparation method according to claim 12, characterized in that: In the hydrogel obtained by the preparation method: the final concentration of the polyvinyl alcohol is 8-12wt%, the final concentration of the metal salt is 0.1-0.5 mol / L, the final concentration of the glycerol is 12-18wt%, and the mass ratio of the glycerol to the water is 2:8.

Citation Information

Patent Citations

  • High-strength strain-sensitive polyvinyl alcohol ion hydrogel sensing material, and preparation method and application thereof

    CN110256697A

  • High-strength and high-toughness anisotropic fiber-based hydrogel, preparation method thereof and ionic conductive hydrogel

    CN115075011A

  • Hydrogels

    CN115429702A